New approach of modeling influential factors of safety climate in industrial companies with a predominantly female labor force - Stefanović, Violeta; Milijić, Nenad; Urošević, Snežana; Mladenović-Ranisavljević, Ivana; Završnik, Bruno (Serbian Journal of Management, 2025)
The research in this paper aims to develop an original model of the influencing factors of the safety climate in industrial processes, as an important element of organizational development. The set of collected data was analyzed by using statistical tool software packages SPSS 21.0 and LISREL 8.80, based on testing a sample of 843 employees of industrial organizations with a predominantly female labore force, in the Republic of Serbia, on the territory of Jablanica District. It was determined that the factors of the working conditions (WC), as well as attitude of employee towards the working conditions (AE), can be indicators of the impact of employee safety. The developed model is a practical, acceptable and applicable solution that can bring positive changes in practice, regarding occupational safety and health (OSH).